"A HATEFUL CAWING FROM THE CROWS": COLLATERAL DAMAGE IN THE CULTURE WARS. Issue 2 (16th May 2018) - Willett, Mischa
Abstract : W. E. Aytoun's satirical verse drama, Firmilian (1854), an anti-radical, scattershot missive meant to re-align British poetic tastes by reversing the aesthetic gains made by Romanticism in the decades prior to its publication, has been called "one of the most successful pieces of literary criticism ever written" (Morton 849). Despite its broad ambitions, however, it has often been read as a narrow attack on the individual poets popular during the summer of its appearance, creating a school where one had not existed before, turning the poets Philip James Bailey, Alexander Smith, Sydney Dobell and others into "the Spasmodic School." But, as Charles LaPorte and Jason Rudy suggest, despite a myth that grew up later in the century about Firmilian's mighty power and the Spasmodic stars' demise, the label hardly destroyed the poets associated therewith. So did Firmilian accomplish its purposes? In what ways can we consider it successful if not?